Community structure of epilithic microalgae in the Upper Setail River, Banyuwangi District, East Java, Indonesia - DIANA ARFIATI; UMI ZAKIYAH; ALFI NUR RUSYDI; MUHAMMAD ZIDAN AL ATHOR; KHARISMA ORCHIDA; ZAKIYYAH NUR INAYAH; WINDA HIMATUL ULYA; AHMAD ALFA SAHAL; RIFQAH RACHMAWATI; TITIS DWI ANDHANI; RIZKY KUSMA PRATIWI (Society for Indonesian Biodiversity, 2025)
Abstract. Arfiati D, Zakiyah U, Rusydi AN, Al Athor MZ, Orchida K, Inayah ZN, Ulya WH, Sahal AA, Rachmawati R, Andhani TD, Pratiwi RK. 2025. Community structure of epilithic microalgae in the Upper Setail River, Banyuwangi District, East Java, Indonesia. Biodiversitas 26: 2309-2319. Setail River is one of the freshwater ecosystems in Banyumas District, East Java, Indonesia, which contains a lot of rocky substrates. This substrate can serve as a site for epilithic microalgae to attach, which act as natural food sources for aquatic organisms and serve as a bioindicator of the aquatic environment. The purpose of this study was to analyze the community structure of epilithic microalgae in the Setail River. This study was carried out from December 2023 to September 2024 using a survey method at 5 sampling points in the Upper Setail River, Banyuwangi District. Epilithic microalgae samples were taken using the quadrant transect method (5x5 cm²) and identified using the Modified Lackey Drop Micro Transect Counting Method. The identified results included 35 genera from 4 divisions of epilithic microalgae. The microalgae divisions are Bacillariophyta (27 genera), Chlorophyta (2 genera), Cyanophyta (3 genera), and Charophyta (3 genera). The abundance of epilithic microalgae is 8,169-21,240 cells/cm². The Bacillariophyta division is the most frequently found division, with a percentage ranging from 83 to 95%. Navicula is the most frequently found genus, with the highest average abundance of 6,225 cells per cm², making it a key indicator of organic pollution in waters. The diversity index ranges from 1.65-2.17 (moderate, H': 1-3), the evenness index ranges from (0.75-0.80) (e>6 high), and the dominance index ranges from 0.17-0.33 (low, C approaching 0). The Saprobic Index analysis obtained in the Setail River waters ranges from 0.60 to 1, indicating that the waters are lightly polluted (?-mesosaprobic), which suggests that only a few pollutants enter from organic and inorganic materials. The lowest saprobic value was found at station 5, indicating that further management of waste input into the river is necessary to prevent severe pollution due to organic and inorganic waste in the Setail River waters.